2012
DOI: 10.1017/s0958344012000079
|View full text |Cite
|
Sign up to set email alerts
|

Using a stance corpus to learn about effective authorial stance-taking: a textlinguistic approach

Abstract: Presenting a persuasive authorial stance is a major challenge for second language (L2) writers in writing academic research. Failure to present an effective authorial stance often results in poor evaluation, which compromises a writer's research potential. This study proposes a ''textlinguistic'' approach to advanced academic writing to complement a typical corpus approach that is oriented toward exploring lexico-grammatical patterns at the sentence level. A web-based stance corpus was developed which allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
(79 reference statements)
0
27
0
Order By: Relevance
“…To sum up, based on the studies related to EScP published in 2008-2012, it is suggested that science instructors should turn teacher-centered courses into student-centered instruction by using data-driven approaches such as the corpus studies by Chang (2012), Lin and Evans (2012) and Soler (2011). Critical reviews on global forums and asynchronous online discussions (AOD) can also shift the paradigm to student-centered instruction (Loncar et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To sum up, based on the studies related to EScP published in 2008-2012, it is suggested that science instructors should turn teacher-centered courses into student-centered instruction by using data-driven approaches such as the corpus studies by Chang (2012), Lin and Evans (2012) and Soler (2011). Critical reviews on global forums and asynchronous online discussions (AOD) can also shift the paradigm to student-centered instruction (Loncar et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, it seems tough in the present education system despite calls for the field to move in this direction (Cargill et al 2012). Second, English-Mediated science instruction and EScP material development should be based on scientific disciplinary culture differences since it provides suitable courses and materials for the target students (Chang 2012;Lin and Evans 2012). As seen in the methodology column in Table 5, students' language needs are often met via corpus studies, which contain the target learner's authentic language needs-the standardized, scientific language used by the international scientific community (Chang 2012;Lin and Evans 2012;Soler 2011).…”
Section: Methodological Analysis On the Studies Of Escp Instruction Tmentioning
confidence: 99%
See 3 more Smart Citations